L’archéologie en question : les pays nordiques - Arwill-Nordbladh, Elisabeth; Demoule, Jean-Paul; Glørstad, Håkon; Kristianson, Kristian; Nilsson Stutz, Liv; Ravn, Mads (Perspective, 2019)
Y a-t-il une spécificité de l’archéologie des pays du Nord de l’Europe ? C’est à un archéologue danois, conservateur de l’Oldnordisk Museum de Copenhague, Christian Jürgensen Thomsen, que nous devons depuis 1836 le « système des trois âges », c’est-à-dire la distinction, fondatrice de la préhistoire européenne et au-delà, entre un âge de la pierre, un âge du bronze et un âge du fer. Dès le xviie siècle, le royaume de Suède avait institué un service archéologique national – il faut attendre le. Is there a specificity of the archaeology of the countries of northern Europe? A Danish archaeologist, a conservative of the Oldnordisk Museum in Copenhagen, Christian Jürgensen Thomsen, has been responsible since 1836 for the ‘three-age system’, that is to say, the distinction, founder of European prehistory and beyond, between an age of stone, an age of bronze and an age of iron. Since the 10th century, Sweden had set up a national archaeological service – we have to wait until.